2003
DOI: 10.1063/1.1540223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water adsorption on microscopic friction force on SrTiO3(001)

Abstract: A friction force microscope study in ultrahigh vacuum was conducted on an atomically flat SrTiO3(001) surface, where SrO and TiO2 domains were distinguished by the difference in friction force. It is revealed that the friction on the SrO became stronger with water adsorption relative to the TiO2 layer. The selective change in friction is attributed to the chemical reaction occurring on the SrO layer, which is supported by the results of x-ray photoelectron spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 10 publications
6
26
0
Order By: Relevance
“…The data for these cells also compiled in Table II on the other hand demonstrates that the latter is a crucial point as the binding energy exhibits a strong coverage dependence, reflecting overall repulsive interactions consistent with the TPD data from Wang et al 3 . A value fairly representing the low-coverage limit is only reached in (2 × 2) cells, and as we will discuss in Section III.C below, it is this limit that is the appropriate one to discuss the Iwahori FFM experiments 6 .…”
Section: A Sro-terminationmentioning
confidence: 99%
See 2 more Smart Citations
“…The data for these cells also compiled in Table II on the other hand demonstrates that the latter is a crucial point as the binding energy exhibits a strong coverage dependence, reflecting overall repulsive interactions consistent with the TPD data from Wang et al 3 . A value fairly representing the low-coverage limit is only reached in (2 × 2) cells, and as we will discuss in Section III.C below, it is this limit that is the appropriate one to discuss the Iwahori FFM experiments 6 .…”
Section: A Sro-terminationmentioning
confidence: 99%
“…(2), of the most stable water adsorption geometries at the different coverages at the SrO-termination (left) and TiO2-termination (right). In the top x-axis, the dependence on the water chemical potential is converted into pressure scales at 300 K and 500 K. The plain (blue) background boxes mark the region of gas-phase conditions probed by Iwahori et al in their FFM experiments 6 , while the dotted (gray) boxes indicate the region above the H2O-rich limit, i.e. where the present approach assuming equilibrium with water vapor is no longer strictly applicable.…”
Section: First-principles Thermodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Iwahori et al confirmed that the major contaminants on SrTiO 3 surfaces exposed to air are carbon species by detecting C 1s signals in XPS spectra. 43 We presume that both H 2 O and hydrocarbon adsorb on the TiO 2 layers, whereas mainly hydrocarbon occupies the SrO layers. Figures 4͑a͒ and 4͑b͒ show STM images taken of the 3°o ff vicinal surface of SrTiO 3 ͑Nb 0.5 wt % doped͒ annealed in UHV at different temperatures.…”
Section: Resultsmentioning
confidence: 90%
“…6͑c͒, which ruled this out. Another thing that possibly happens is that the water adsorbed reacted with the SrO layer 31,43 and changed its elastic properties. But, again this cannot explain the huge difference observed.…”
Section: Resultsmentioning
confidence: 99%